An influence of classical dance on a technical preparedness level of athletes in acrobatic rock and roll at the preliminary basic training stage - Кизім, Петро; Гуменюк, Сергій; Батєєва, Наталія (Slobozhanskyi Herald of Science and Sport, 2017)
Petro Kyzim, Serhii Humeniuk & Nataliya Batieieva Purpose: experimentally substantiate the technique for improving the technical training of acrobatic rock'n'roll athletes with classical dance at the stage of preliminary basic training. Material & Methods: the following research methods were used: theoretical analysis and generalization of data from special scientific and methodological literature; pedagogical observation; pedagogical testing; method of expert evaluation; methods of mathematical statistics. Expert assessment of 12 sports couples (12 male partners and 12 female partners) before and after the research. Results: on the basis of the evaluation scale (Rules of the WRRC, 2017), the estimated results of the performance of the competition program were obtained. Dynamics of the level of technical mastery of performance of competitive programs is determined separately for each sports pair of athletes. Conclusion: found that the use of classical dance means significantly affect the level of technical training of athletes in acrobatic rock'n'roll.